Short-term, medium-term, and long-term risks of nonvariceal upper gastrointestinal bleeding after dengue virus infection - Yu-Wen Chien; Hui-Ning Chuang; Yu-Ping Wang; Guey Chuen Perng; Chia-Yu Chi; Hsin-I Shih (Public Library of Science (PLoS), 2022)
Dengue patients have an increased risk of acute gastrointestinal (GI) bleeding. However, whether dengue virus (DENV) infection can cause an increased long-term risk of GI bleeding remains unknown, especially among elderly individuals who commonly take antithrombotic drugs. A retrospective population-based cohort study was conducted by analyzing the National Health Insurance Research Databases. Laboratory-confirmed dengue patients from 2002 to 2012 and four matched nondengue controls were identified. Multivariate Cox proportional hazard regression was used to evaluate the acute (<30 days), medium-term (31-365 days), and long-term (>365 days) risks of nonvariceal upper GI bleeding after DENV infection. Stratified analyses by age group (≤50, 51-64, ≥65 years old) were also performed. In total, 13267 confirmed dengue patients and 53068 nondengue matched controls were included. After adjusting for sex, age, area of residence, comorbidities, and medications, dengue patients had a significantly increased risk of nonvariceal upper GI bleeding within 30 days of disease onset (adjusted HR 55.40; 95% CI: 32.17-95.42). However, DENV infection was not associated with increased medium-term and long-term risks of upper GI bleeding overall or in each age group. Even dengue patients who developed acute GI bleeding did not have increased medium-term (adjusted HR; 0.55, 95% CI 0.05-6.18) and long-term risks of upper GI bleeding (adjusted HR; 1.78, 95% CI 0.89-3.55). DENV infection was associated with a significantly increased risk of nonvariceal upper GI bleeding within 30 days but not thereafter. Recovered dengue patients with acute GI bleeding can resume antithrombotic treatments to minimize the risk of thrombosis. Author summary Dengue fever is a mosquito-borne tropical disease caused by the dengue virus. Dengue patients can have low platelet counts and might have acute gastrointestinal bleeding (tarry stool, bloody stool or bloody vomiting). Most dengue patients will fully recover and return to their previous health levels. Previous studies have indicated that some dengue patients have persistent low platelet counts and high inflammatory responses. The medium-term and long-term upper gastrointestinal bleeding risks remain unknown. Our study suggested that dengue was significantly associated with an increased risk of nonvariceal upper GI bleeding within 30 days after infection but was not associated with increased medium-term (31-365 days) and long-term risks (>365 days) of upper GI bleeding. Therefore, the risk of acute gastroenterology bleeding returned to baseline levels after 30 days. Recovered dengue patients with acute GI bleeding can resume antiplatelet, antithrombotic, and oral anticoagulation (OAC) treatments.